Sunday

March 1, 2015

March 1, 2015

Posted by **lindsay** on Thursday, July 10, 2014 at 10:22am.

- math -
**Steve**, Thursday, July 10, 2014 at 10:44am10^(2x+1) -7(10^x) -26 = 0

10*10^2x - 7*10^x - 26 = 0

10*10^(2*2log t) - 7*10^(2log t) - 26 = 0

10*10^(4log t) - 7*10^(2log t) - 26 = 0

10*(10^(log t))^4 - 7*(10^(log t))^2 - 26 = 0

10t^4 - 7t^2 - 26 = 0

(10t^2+13))(t^2-2) = 0

t = ±√2 or ±√(13/10) i

**Answer this Question**

**Related Questions**

Math - Express as a single logarithm. 1/2log(subscript)3 144-log(subscript)3 4+...

algebra - equivalent expression for 2log(x+1)-2log(x-1)-log(x-1)

math - Q1:solve log(5)x-log(25)(x+10) = 0.5 Q2:If 2log(a)x=1+log(a) (7x-10a) ,...

Precalculus - What am I doing wrong? I keep getting 48 and its wrong... Solve ...

algebra - does log base of 4 sqrt(t/s)=1/2log base of 4 t - 1/2log base of 4s? ...

Math quick help anyone - 1. I'm given a slope of 1/4 and a set of 2 points each...

math - 6^(2log(x)) = 8

Calculus-HELP PLZ !!!! - Find a general solution to the first – degree ODE. If ...

Calculus - Find a general solution to each first ¨C degree ordinary differential...

Calculus-HELP!!! - Find a general solution to the first – degree ordinary ...